Pattern Transformations: Supporting Learning of Symbolic Representations Among TVET Trainees - Yasak, Zurina; Alias, Maizam (Journal of Technical Education and Training, 2020)
Symbolic representations are a form of language that is routinely used in technical communications. Trainees in Technical and Vocational Education (TVE) are thus, expected to master symbolic representations concurrently with skills acquisition.  Electrical circuit diagram is an example of symbolic representations in use to communicate information on the components and working concepts of an electrical circuit.  Mastering symbolic representations in circuit diagram however, can be challenge to some which often lead to miscommunications and poor job performance. Problems are further compounded when trainees need to learn symbols associated with abstract concepts. Inability to master the â€œsymbols languageâ€ if remain unchallenged will impact subsequent learning. Appropriately designed instructional materials to address learning of symbolic representations are thus crucial. The aim of this paper is to assess the efficacy of two instructional materials for learning symbolic representations and electrical concepts. A quasi-experimental study with three groups of TVE trainees participated in this study. One group used the existing learning materials (control) while the other two groups used specifically designed pattern transformation materials that are available in two media, print-based and video-based materials. Overall, both experimental groups achieved greater learning on symbolic representations and concepts compared to the control group. Equivalent status was also observed among the experimental groups. This indicates that pattern transformation materials irrespective of media used can be effective at learning symbolic representations in electrical related content.